Applications of nanomaterials for gastrointestinal tumors: A review - Kanaoujiya, Rahul; Porwal, Dipiti; Srivastava, Shekhar (Frontiers in Medical Technology, 2022)
Nanotechnology is the emerging and advance field of research for the diagnosis and treatment of various diseases. With the development of nanotechnology, different nanoparticles are used in the treatment of cancer due to their unique optical properties, excellent biocompatibility, surface effects, and small size effects. Nanoparticles are the particles which have the particular size from 1 to 100 nm. These nanoparticles are zero dimension, one dimension, two dimension and three dimension etc. In present scenario a variety of research is focused on the tailored synthesis of nanoparticles for medicinal applications that can be used for cancer treatment based on the morphology, composition, interaction with target cell. The gastrointestinal (GI) tumors are found one of the deadest cancer types with highest reoccurrence rates. The diagnosis and treatment of gastrointestinal cancer is very challenging due to its deep location and complicated surgery. Nanotechnology provides fast diagnosis and immediate treatment for the gastrointestinal disease. A variety of nanomaterials are used for the diagnosis and treatment of GI disease. Nanoparticles target directly to the tumor cell as diagnostic and therapeutic tools facilitating the identification and removal of tumor cells. A number of nanoparticles are developed for the uses are quantum dots (QDs), carbon nanotubes (CNTs), metallic nanoparticles (MNPs), Dendrimers etc. This review article gives an overview of the most promising nanomaterials used for the diagnosis and treatment of GI diseases. This review attempts to incorporate numerous uses for the most current nanomaterials, which have great potential for treating gastrointestinal diseases.